PD-L1 expression in tumor tissue and peripheral blood of patients with oral squamous cell carcinoma - Weber, Manuel; Wehrhan, Falk; Baran, Christoph; Agaimy, Abbas; Büttner-Herold, Maike; Preidl, Raimund; Neukam, Friedrich Wilhelm; Ries, Jutta (Oncotarget, 2017)
Immune checkpoints like programmed cell death-1 (PD-1) and its ligand PD-L1 are involved in immune escape mechanisms of solid tumors including oral squamous cell carcinoma (OSCC). Inhibitors of the pathway are successfully used for treating especially advanced disease. However, the physiological relevance of PD-1/PD-L1-signaling in OSCC is insufficiently understood. The aim of the study was to analyze if PD-L1 expression in tumor tissue and peripheral blood samples of OSCC patients is associated with histomorphological tumor parameters and if PD-L1 expression in patients is different from controls.OSCC tumor specimens showed a significantly higher PD-L1 expression than oral mucosa controls (p < 0.001; upregulation more than 3-fold). Cross-tabulation revealed an association of increased expression of PD-L1 mRNA in tissue specimens with malignancy (p < 0.001).OSCC cases with higher tumor grade and cases with lymph node metastases (N+) were significantly (p < 0.05) associated with increased PD-L1 expression in peripheral blood. Cross-tabulation revealed an significant association with lymph node metastases (N+) (p <= 0.002).PD-L1 mRNA expression was analyzed in tumor specimens and corresponding samples of healthy oral mucosa and peripheral blood of 45 OSCC patients and 36 healthy control persons using RT-qPCR analysis. A Mann-Whitney U-test, a cut-off point analysis and a Chi-square test were carried out.PD-L1 expression in OSCC could contribute to the immunosuppressive local tumor microenvironment. Increased malignant behavior (higher tumor grade, positive nodal status) might be associated with PD-L1 mediated systemic immune tolerance. Thus, PD-L1 expression in peripheral blood might be an indicator of the existence of metastatic disease (N+) in OSCC.
EVALuna2:25563